Maturation arrest in early postnatal sensory receptors by deletion of the miR-183/96/182 cluster in mouse - Fan, Jianguo (Proc Natl Acad Sci U S A, 2017)
The polycistronic miR-183/96/182 cluster is preferentially and abundantly expressed in terminally differentiating sensory epithelia. To clarify its roles in the terminal differentiation of sensory receptors in vivo, we deleted the entire gene cluster in mouse germline through homologous recombination. The miR-183/96/182 null mice display impairment of the visual, auditory, vestibular, and olfactory systems, attributable to profound defects in sensory receptor terminal differentiation. Maturation of sensory receptor precursors is delayed, and they never attain a fully differentiated state. In the retina, delay in up-regulation of key photoreceptor genes underlies delayed outer segment elongation and possibly mispositioning of cone nuclei in the retina. Incomplete maturation of photoreceptors is followed shortly afterward by early-onset degeneration. Cell biologic and transcriptome analyses implicate dysregulation of ciliogenesis, nuclear translocation, and an epigenetic mechanism that may control timing of terminal differentiation in developing photoreceptors. In both the organ of Corti and the vestibular organ, impaired terminal differentiation manifests as immature stereocilia and kinocilia on the apical surface of hair cells. Our study thus establishes a dedicated role of the miR-183/96/182 cluster in driving the terminal differentiation of multiple sensory receptor cells.